Influence of pacing manipulation on performance of juniors in simulated 400-m swim competition - Skorski, S.; Faude, O.; Abbiss, C. R.; Caviezel, S.; Wengert, N.; Meyer, T. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To date, there has been limited research examining the influence of pacing pattern (PP) on middle-distance swimming performance. As such, the purpose of the current study was to examine the influence of PP manipulation on 400-m freestyle swimming performance. Methods: 15 front-crawl swimmers (5 female, 10 male; age 18 ± 2 y) performed 3 simulated 400-m swimming events. The initial trial was self-selected pacing (PPSS). The following 2 trials were performed in a counterbalanced order and required participants to complete the first 100 m more slowly (PPSLOW: 4.5% ± 2.2%) or quickly (PPFAST: 2.4% ± 1.6%) than the PPSS trial. 50-m split times were recorded during each trial. Results: Overall performance time was faster in PPSS (275.0 ± 15.9 s) than in PPFAST (278.5 ± 16.4 s, P = .05) but not significantly different from PPSLOW (277.5 ± 16.2 s, P = .22). However, analysis for practical relevance revealed that pacing manipulation resulted in a "likely" (>88.2%) decrease in performance compared with PPSS. Conclusion: Moderate manipulation of the starting speed during simulated 400-m freestyle races seems to affect overall performance. The observed results indicate that PPSS is optimal in most individuals, yet it seems to fail in some swimmers. Future research should focus on the identification of athletes possibly profiting from manipulations.